Essence of partnership management in project-based learning: insights from a university's global project programme. Issue 2 (28th October 2020) - Pan, Gary; Seow, Poh-Sun; Shankararaman, Venky; Koh, Kevin
Abstract : Purpose: Although it is clear that there are many benefits of academic–industry partnership through project-based learning (PBL) courses offered by universities, however, there are challenges in establishing such partnerships that if not addressed, may result in either failure of such collaboration or an unpleasant experience for parties involved. Accordingly, this study aims to address this knowledge gap in the PBL literature by identifying the essence of partnership management and offering insights to managing such partnerships effectively. Design/methodology/approach: This study aims to develop a framework that highlights the essence of partnership management in a PBL setting and validate the framework by conducting a focus group study on a university in Singapore (UNIS)'s PBL programmes called UNIS-X and UNIS-XO. Findings: The results suggest that the key features of partnership management include a value proposition, depth of collaboration, knowledge creation and exchange and continuous feedback. In addition, the findings offer useful insights to managing effective partnerships when engaging industry partners in a PBL programme. Originality/value: For researchers, this paper contributes to the PBL literature by identifying and validating the key features of effective partnerships in PBL. This serves as one of the first exploratory and validation studies in examining key features of partnership in the PBL literature. For educators, this study offers useful insights to understanding effective partnership management when engaging industry partners in a PBL course. With the knowledge, educators can devise useful actions to ensure these features of a partnership are established and maintained throughout the project.